Penguatan Fleksibilitas Sumber Daya Manusia Sebagai Pelaku Usaha Mikro, Kecil, Dan Menengah Dalam Menghadapi Dinamika Bisnis Era Digital. - Zhafira, Nabila Hilmy; Husen, Tamitha Intassar; Ertika, Yenny; Devilishanti, Tio; Chairiyaton, Chairiyaton (Jurnal Pengabdian Agro and Marine Industry, 2025)
Micro, small and medium enterprises (MSMEs) face challenges that continue to change along with technological developments and market dynamics. The service activity underlying this paper focuses on strengthening the adaptive and  flexibility of human resources (HR) of women MSME practitioner in Banda Aceh. The main objective of this activity is to improve the ability of MSME  practitioner to manage their businesses strategically, utilize social media, and develop an adaptive mindset to change. Through material delivery methods and interactive discussions, participants were encouraged to determine business priorities, use digital platforms that match the character of the product, and build courage in facing new challenges. The results of the activity show that this approach is effective in encouraging the improvement of managerial skills and mental readiness of MSME  practitioner to develop more competitively. Therefore, HR coaching can be a strategic step in strengthening the competitiveness of MSMEs in a sustainable manner.